2020
DOI: 10.33448/rsd-v9i11.9488
|View full text |Cite
|
Sign up to set email alerts
|

Importância do conhecimento anatômico na Síndrome de Eagle: relato em crânio secos

Abstract: O processo estilóide é uma projeção óssea e pontiaguda que se origina do osso temporal e seu comprimento padrão varia entre 25 a 30 mm. Quando este comprimento é excedido, o acidente ósseo é considerado alongado, isso associado a sintomatologia específica pode indicar o diagnóstico de Síndrome de Eagle. Esse relato foi um achado anatômico, observacional, realizado a partir de osteotécnica em crânios secos de adultos, pertencentes ao laboratório de Anatomia Humana da Universidade Federal do Paraná - Campus Tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The cases in which the elongated styloid process was presented bilaterally were more prevalent in our study (54%) and, although no statistically significant difference was observed, this finding is in agreement with several other studies found in the literature, where the authors state that when comparing the affected side, taking into account the form of unilateral or bilateral involvement, the highest prevalence observed occurs in the bilateral form (SOUZA et al, 2020;ALZAREA, 2017;MUÑOZ-LEIJA et al, 2020;BUYUK;GUNDUZ;AVSEVER, 2018;CHU et al, 2022;CAVALCANTE et al, 2017;GRACCO et al, 2017;GUIMARÃES et al, 2010;CARVALHO et al, 2021). However, although in smaller numbers, there is also a report in the literature of a study conducted where the form of unilateral involvement was more prevalent (GOVINDARAJALU; SHARMA; PARSANA, 2020), as well as a study where no predilection for the uni or bilateral form was observed (SOUZA et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The cases in which the elongated styloid process was presented bilaterally were more prevalent in our study (54%) and, although no statistically significant difference was observed, this finding is in agreement with several other studies found in the literature, where the authors state that when comparing the affected side, taking into account the form of unilateral or bilateral involvement, the highest prevalence observed occurs in the bilateral form (SOUZA et al, 2020;ALZAREA, 2017;MUÑOZ-LEIJA et al, 2020;BUYUK;GUNDUZ;AVSEVER, 2018;CHU et al, 2022;CAVALCANTE et al, 2017;GRACCO et al, 2017;GUIMARÃES et al, 2010;CARVALHO et al, 2021). However, although in smaller numbers, there is also a report in the literature of a study conducted where the form of unilateral involvement was more prevalent (GOVINDARAJALU; SHARMA; PARSANA, 2020), as well as a study where no predilection for the uni or bilateral form was observed (SOUZA et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The apex of the styloid process reaches the posterior edge of the mandible ramus serving as support to the stylohyoid, stylopharyngeal, and styloglossal muscles (ALZAREA, 2017;PEREIRA et al, 2022;SAMPAIO et al, 2021;SOUZA et al, 2020). In it are still inserted the stylohyoid ligaments (which connect the styloid process to the hyoid bone, and the stylo-mandibular ligament) that extends to the angle of the mandible (BORGES et al, 2021;FERNANDES et al, 2016;GUIMARÃES et al, 2010;GRACCO et al, 2017;LINDENBLATT et al, 2018;MUÑOZ-LEIJA et al, 2020).…”
Section: The Styloid Process and Associated Structuresmentioning
confidence: 99%
See 2 more Smart Citations